Pharmacological advances in pemphigoid. (June 2019) - Maglie, Roberto; Hertl, Michael
Highlights: Conventional immunosuppressive therapies in pemphigoid are associated with increased morbidity and mortality. Doxycycline has the potential of a suitable first line therapy in milder cases of BP, with lower side effects than systemic steroids. Various targeted therapies are now available for refractory patients. Monoclonal antibodies targeting eotaxin, interleukin (IL)-4, IL-5, and IL-17 are currently tried in clinical studies. Targeting complement activation has shown promise in experimental studies. Abstract : Pemphigoid is the most common autoimmune blistering disease. IgG and IgE autoantibodies against the hemidesmosomal antigens Bullous Pemphigoid (BP) 180 and BP230 are of pathogenic relevance, since autoantibody–antigen binding results in complement activation, immune cells infiltration, impaired hemidesmosomal function, and loss of dermal–epidermal adhesion. Systemic steroids and immunosuppressants are frontline therapies in pemphigoid, but result in substantial morbidity and increased mortality. A large randomized multicenter study highlighted doxycycline as a feasible alternative to systemic corticosteroids in patients not suitable for long-term steroid use. In recent years, new targeted therapies, including intravenous immunoglobulin (IvIg), rituximab, omalizumab, and immunoadsorption, have proven efficacy in the refractory setting, but, with the exception of IVIG, large randomized trial has not been performed yet. Basic research studies have now shed light on the pathogenic role of eosinophils and autoreactive T-helper 2 cells in pemphigoid, inducing tissue damage and sustaining autoantibody production by autoreactive B-cells, respectively. Indeed, eosinophils and Th2-related cytokines have become attractive therapeutic options. Moreover, Interleukin-17 related inflammatory pathways have been also shown to participate in the blistering process. This review discusses current evidence for the use of targeted therapies in pemphigoid as well as most relevant pharmacologic advances and new drugs currently under clinical investigation.